Untangling outcomes of de jure and de facto community-based management of natural resources - Agarwala, M.; Ginsberg, J.R. (Wiley, 2017)
We systematically reviewed the literature on the tragedy of the commons and common‐property resources. We segregated studies by legal management regimes (de jure regimes) and management that develops in practice (de facto regimes) to understand how the structure of regime formation affects the outcome of community management on sustainability of resource use. De facto regimes, developed within the community, are more likely to have positive impacts on the resource. However, de facto regimes are fragile and not resilient in the face of increased population pressure and unregulated markets, and de facto management regimes are less successful where physical exclusion of external agents from resources is more difficult. Yet, formalization or imposition of de jure management regimes can have complicated impacts on sustainability. The imposition of de jure regimes usually has a negative outcome when existing de facto regimes operate at larger scales than the imposed de jure regime. In contrast, de jure regimes have largely positive impacts when the de facto regimes operate at scales smaller than the overlying de jure regimes. Formalization may also be counterproductive because of elite capture and the resulting de facto privatization (that allows elites to effectively exclude others) or de facto open access (where the disenfranchised may resort to theft and elites cannot effectively exclude them). This underscores that although the global movement to formalize community‐management regimes may address some forms of inequity and may produce better outcomes, it does not ensure resource sustainability and may lead to greater marginalization of users. Comparison of governance systems that differentiate between initiatives that legitimize existing de facto regimes and systems that create new de facto regimes, investigations of new top‐down de jure regimes, and studies that further examine different approaches to changing de jure regimes to de facto regimes are avenues for further inquiry.